David against Goliath? The rise of coastal states at the Indian Ocean Tuna commission - Sinan, Hussain; Andriamahefazafy, Mialy; Robertson, Kerrie (Frontiers in Marine Science, 2022)
Tuna regional fisheries management organizations (RFMOs) have long suffered from the domination of distant water fishing nations (DWFNs) in decision-making processes. The Indian Ocean Tuna Commission (IOTC) is no exception. In recent years, coastal states of the Indian Ocean (IO) have tried to change this dynamic - led by countries like the Maldives, Kenya, South Africa, and Australia - to deliver greater benefits to the region, including East Africa. These countries are gathered under the informal group of G16 and have increasingly improved their involvement in the IOTC. Here, we ask how the rise of the G16 benefited coastal States through participation and collective understanding in the Indian Ocean. To do this, we analyzed proposals submitted by the G16 for conservation and management measures and the participant lists of the Commission meetings in the past ten years. Our results show that, individually and collectively, the G16 has played a significant role in shaping the IOTC’s rules. The coastal States have established a good representation, with only a handful of Members absent in some years. Unveiling the efforts of coastal countries is essential to guide further capacity building in the region in terms of negotiations. We also call for international oversight of the actions of DWFNs, such as the EU, whose efforts often differ markedly from their claims of being sustainability champions. The G16’s work is essential to keep the coastal States of the Indian Ocean in the driver’s seat for managing Indian Ocean fisheries to benefit future generations.